It had to be you : the Gossip Girl prequel / Cecily Von Ziegesar - Von Ziegesar, Cecily
Reveals the effects on a trio of bright, attractive, fifteen-year-old friends--Serena van der Woodsen, Blair Waldorf, and Nate Archibald--when Serena considers leaving their seemingly-perfect life of luxury in New York's Upper East Side for boarding school.